Menelusuri Tradisi Horja Patibal Sere sebagai Warisan Budaya Suku Mandailing di Panyabungan, Mandailing Natal - Sepriani, Laila; Rohani, Laila (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
This study aims to examine the Horja Patibal Sere tradition among the Mandailing ethnic group in Panyabungan, Mandailing Natal Regency. Employing a qualitative research method, the study utilized in-depth data collection through observation, interviews, documentation, and data analysis techniques. The findings reveal that Patibal Sere is a compulsory customary ritual held at night, involving family members, religious figures, and traditional leaders. During the ceremony, the agreed-upon mahar (bridal dowry) is presented on a ceremonial tray along with symbolic items such as burangir (betel leaves), yellow rice, areca nut, banana leaf tips, and a traditional long cloth. Following the symbolic handover, the bride’s mother carries the dowry, representing a gesture of nurturing, protecting, and caring for the continuity of the marriage. The Mandailing people, an ethnic group from North Sumatra, possess a rich and distinctive cultural heritage. The Patibal Sere tradition, passed down for generations, remains an essential component of the customary marriage rites. It reflects the deep-rooted values, identity, and social cohesion within the Mandailing community, particularly emphasizing the sacredness and communal nature of marriage through ancestral rituals.‎